The Challenges of Spirometric Diagnosis of COPD - Adriana Maldonado-Franco; Luis F. Giraldo-Cadavid; Eduardo Tuta-Quintero; Alirio R. Bastidas Goyes; Daniel A. Botero-Rosas (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is one of the top causes of morbidity and mortality worldwide. Although for many years its accurate diagnosis has been a focus of intense research, it is still challenging. Due to its simplicity, portability, and low cost, spirometry has been established as the main tool to detect this condition, but its flawed performance makes it an imperfect COPD diagnosis gold standard. This review aims to provide an up-to-date literature overview of recent studies regarding COPD diagnosis; we seek to identify their limitations and establish perspectives for spirometric diagnosis of COPD in the XXI century by combining deep clinical knowledge of the disease with advanced computer analysis techniques.